Counterfactual impact evaluation of cohesion policy. Work package 2: Examples from support to innovation and research. Final report - Dirk Czarnitzki; Cindy Lopes Bento; Thorsten Doherr (Katholieke Universiteit, 2011)
The goal of this project was twofold. The first objective was to find out to what extent publicly available beneficiary data (from managing authorities and commercial databases) could be used for quantitative, econometric counterfactual analysis. This led to a second objective: in the countries and regions where data was most promising, a treatment effects analysis of the impacts of Cohesion Policy on innovation activities at the firm level has been conducted.
Keywords: 330; EU Regional Policy; Effect Analysis; Czech Republic; France; Germany; EU-Regionalpolitik; Wirkungsanalyse; Tschechien; Frankreich; Deutschland